2016
DOI: 10.1111/apt.13711
|View full text |Cite
|
Sign up to set email alerts
|

Liver stiffness measurement reliability and main determinants of point shear‐wave elastography in patients with chronic liver disease

Abstract: Point quantification shear-wave elastography reliably and reproducibly evaluates liver stiffness, matching transient elastography for accuracy after a 1-year learning curve or 130 examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…In line with our findings, a recent study comparing Philips ElastoPQ technology with Fibroscan having histology as a reference standard, showed an acceptable precision of Philips ElastoPQ (r = 0.67), but the thresholds were lower than those of Fibroscan for the same fibrosis stages [15]. In fact, in that case series of 186 patients, only 4 patients showed ElastoPQ values >20 kPa as compared with 15 patients who underwent Fibroscan.…”
Section: Discussionsupporting
confidence: 90%
“…In line with our findings, a recent study comparing Philips ElastoPQ technology with Fibroscan having histology as a reference standard, showed an acceptable precision of Philips ElastoPQ (r = 0.67), but the thresholds were lower than those of Fibroscan for the same fibrosis stages [15]. In fact, in that case series of 186 patients, only 4 patients showed ElastoPQ values >20 kPa as compared with 15 patients who underwent Fibroscan.…”
Section: Discussionsupporting
confidence: 90%
“…Echosens, the manufacturer of the FibroScan device, recommends that TE be performed by an experienced operator (> 100 examinations). Using liver biopsy as the reference standard, a recent study has shown that ElastPQ ® matched TE for accuracy after the operator had performed at least 130 examinations [93].…”
Section: Operator Experiencementioning
confidence: 99%
“…The latter combines measures of both precision and accuracy to determine how far the observed data deviate from the line of perfect concordance (i.e., the line at 45 degrees on a square scatterplot). Cutoffs different from those of TE have been reported for other pSWE elastography products as well [12][13][14]. We hypothesize that this difference may be due to the difference in the push pulse between the two techniques and to the different direction of the shear wave propagation.…”
Section: Discussionmentioning
confidence: 68%